Effect of physical parameters and amino acids on phenanthrene degradation ability of bacteria isolated from oil contaminated soils - Dr. PRAVEEN REDDY P (International Journal of Pharma and Bio Sciences, 2019)
Petroleum products contain a wide variety of polyaromatic hydrocarbons (PAHs). These PAHs enter into the environment through various routes. PAHs pollute the environment and some are highly toxic which cause deleterious effects to humans. Phenanthrene is such a PAH occurring in petroleum products. Physical and chemical methods presently used to remove PAHs from polluted sites are ineffective and costly. Bioremediation which employs microbes for metabolizing PAHs is effective in the removal of PAHs from contaminated sites. Due to the simple structure of phenanthrene and its resemblance to many toxic PAHs, it is considered as modelled compound for biodegradation (metabolism) studies of PAHs. In the present study, physical parameters required for the phenanthrene biodegradation activity of fourteen bacteria isolated from oil contaminated soils of mechanical workshops were optimized using M9 minimal medium supplemented with phenanthrene as a sole carbon and energy source. And also the effect of selected amino acids on phenanthrene degradation activity of bacterial isolates was studied. All the bacterial isolates exhibited maximum phenanthrene degradation activity at pH 7.0 within a temperature range of 300C to 350C in the presence of methionine. The Bacillus species (D1) was found to possess the highest phenanthrene biodegradation activity. These bacteria can be improved further and can be exploited for the bioremediation of polluted sites